2011
DOI: 10.1074/jbc.m111.255042
|View full text |Cite|
|
Sign up to set email alerts
|

Src Subfamily Kinases Regulate Nuclear Export and Degradation of Transcription Factor Nrf2 to Switch Off Nrf2-mediated Antioxidant Activation of Cytoprotective Gene Expression

Abstract: Nrf2 (NF-E2-related factor 2) is a nuclear transcription factor that in response to chemical and radiation stress regulates coordinated induction of a battery of cytoprotective gene expressions leading to cellular protection. In this study, we investigated the role of Src kinases in the regulation of Nrf2 and downstream signaling. siRNA-mediated inhibition of Fyn, Src, Yes, and Fgr, but not Lyn, in mouse hepatoma Hepa-1 cells, led to nuclear accumulation of Nrf2 and up-regulation of Nrf2 downstream gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Sub-cellular protein trafficking and localisational control of NRF2 is a key element in the regulation of NRF2 mediated antioxidant response (Jain et al, 2005;Theodore et al, 2008). The localisational control and compartmentalisation of NRF2 has also been linked to its protein stability (Itoh et al, 2003;Niture et al, 2011), a key element that we found to be different in our cell line models. Hence, to extend our line of investigation, we next perturbed the redox balance within the cells and in parallel, studied its effects on NRF2 localisation in cell dependent manner.…”
Section: Distinct Cellular Response Of Cancer Cells To Redox Perturbamentioning
confidence: 73%
“…Sub-cellular protein trafficking and localisational control of NRF2 is a key element in the regulation of NRF2 mediated antioxidant response (Jain et al, 2005;Theodore et al, 2008). The localisational control and compartmentalisation of NRF2 has also been linked to its protein stability (Itoh et al, 2003;Niture et al, 2011), a key element that we found to be different in our cell line models. Hence, to extend our line of investigation, we next perturbed the redox balance within the cells and in parallel, studied its effects on NRF2 localisation in cell dependent manner.…”
Section: Distinct Cellular Response Of Cancer Cells To Redox Perturbamentioning
confidence: 73%
“…In addition, in the nucleus there are other Nrf2 negative regulators. In particular it has been reported that all the four Src subfamily members, including Fyn, Src, Yes, and Fgr follow Nrf2 in the nucleus, phosphorylate Nrf2Tyr568 that leads to nuclear export and ubiquitination/degradation of Nrf2 [68]. Furthermore, there is evidence that the transcription factor Bach1 is a further negative regulator of Nrf2 since it has been reported to compete with Nrf2 for binding to ARE [69].…”
Section: The Keap1-nrf2 Pathwaymentioning
confidence: 98%
“…Finally, Nrf2 induces the expression of several oxidant-signaling proteins that affect particular cellular functions such as autophagy [64], inflammation [65], inflammasome signaling [66], ER stress and UPR [67], apoptosis [14] and mitochondrial biogenesis [15]. 8 There is evidence that persistent accumulation of Nrf2 in the nucleus is harmful; to avoid accumulation of Nrf2 in the nucleus, cells contain mechanisms that autoregulate cellular abundance of Nrf2 [45,68,69]. As recently reviewed by Niture et al [45], the complex Keap1/Cul3-Rbx1 is present not only in the cytosol, but also in the nucleus where it degrades Nrf2 and therefore controls the 'switching off' of Nrf2-activated gene expression.…”
Section: The Keap1-nrf2 Pathwaymentioning
confidence: 99%
“…After discovering Fyn's role in regulating Nrf2, Jaiswal's group further investigated roles of other Src kinase subfamily members (Src, Yes and Fgr) and the Lyn subfamily for controlling Nrf2 gene expression. They elucidated that all four Src subfamily kinases (Src, Yes, Fyn and Fgr) but not Lyn phosphorylate Nrf2 Tyr568 and lead to the nuclear export, ubiquitination and degradation of Nrf2 [20]. While there is controversy as to the direct interaction of GSK-3β with Nrf2, these data still indicate that when Typically, Nrf2 is sequestered to the cytoplasm through binding with Keap1 and continually shuttled to the proteasome for degradation.…”
Section: Regulation Of Nrf2mentioning
confidence: 98%
“…(5) GSK-3β then activates Src kinases, allowing for their translocation into the nucleus. (6) These Src kinases phosphorylate Nrf2 Tyr568 which allows for nuclear export, (7) ubiquitination and degradation of Nrf2 [20]. (8) However, if the insulin receptor signaling is initiated, GSK-3β activity is inhibited [17].…”
Section: Regulation Of Nrf2mentioning
confidence: 99%